Program Bimbel dalam Upaya Meningkatkan Minat Belajar Bahasa Arab Siswa Usia Sekolah Dasar di Desa Karangmalang Wetan - Afifi Dzikro Khisan; Muhammad Ichrom; Raditya Ivan Pambudi; Saifur Rosid Al Mubarok; Dyah Islamiati (Jurnal Pelayanan Masyarakat, 2024)
Understanding the development of Arabic through interest in learning for students is one of the important and useful things for the future. Understanding Arabic is also one of the keys to mastering foreign languages, especially in this developing era. This research method uses empirical type research that uses field data as a data source, for example the results of interviews, observations and documentation. This research uses a qualitative approach, which is a research procedure that produces descriptive data in the form of written or spoken words from people or observable behavior. The results of this study indicate that the program run can increase learning interest in the development of Arabic language of the students by using several teaching methods both interactively and combined.